2019
DOI: 10.1002/hep4.1312
|View full text |Cite
|
Sign up to set email alerts
|

Murine Liver Organoids as a Genetically Flexible System to Study Liver Cancer In Vivo and In Vitro

Abstract: The rising incidence of cholangiocarcinoma (CCA) coupled with a low 5‐year survival rate that remains below 10% delineates the urgent need for more effective treatment strategies. Although several recent studies provided detailed information on the genetic landscape of this fatal malignancy, versatile model systems to functionally dissect the immediate clinical relevance of the identified genetic alterations are still missing. To enhance our understanding of CCA pathophysiology and facilitate rapid functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 27 publications
0
29
0
Order By: Relevance
“…Furthermore, CCA organoids have been shown to be a reliable system for drug testing and personalized medicine applications, and possess an almost negligible capacity to differentiate into hepatocytes 76,245 . As an alternative method, CCA organoids can be established by inducing genetic mutations in healthy organoids via viral transduction and CRISPR-Cas9 genome editing approaches, thus enabling the characterization and elucidation of the roles of oncogenes and/or tumour suppressor genes, either alone or in combination, in cholangiocarcinogenesis 76,246 .…”
Section: Immunobiologymentioning
confidence: 99%
“…Furthermore, CCA organoids have been shown to be a reliable system for drug testing and personalized medicine applications, and possess an almost negligible capacity to differentiate into hepatocytes 76,245 . As an alternative method, CCA organoids can be established by inducing genetic mutations in healthy organoids via viral transduction and CRISPR-Cas9 genome editing approaches, thus enabling the characterization and elucidation of the roles of oncogenes and/or tumour suppressor genes, either alone or in combination, in cholangiocarcinogenesis 76,246 .…”
Section: Immunobiologymentioning
confidence: 99%
“…Using the CRISPR/Cas9 technology, normal intestinal organoids were transformed by sequential introduction of cancer driver gene mutations [90]. Two recent studies reported the generation of organoid models based on chol-orgs that acquire tumorigenic features following genetic modification to incorporate mutations commonly found in CCCs [91,92]. Remarkably, transplantation of such engineered organoids into immunodeficient mice gave rise to xenografts with carcinoma features with characteristics of either HCC or CCC depending on the inserted oncogenic driver.…”
Section: Primary Liver Cancermentioning
confidence: 99%
“…To directly test the impact of E2/Esr2b signaling on hepatoblast differentiation and to determine the conservation of the roles of E2 signaling in hepatobiliary development across species, we utilized bipotent hepatoblasts derived from human induced pluripotent stem cells (iPSCs). These progenitor cells are capable of differentiating into hepatocytes and BEC/cholangiocytes as assayed by albumin and CK7 expression, ( 34 ) respectively (Fig. 5A).…”
Section: Resultsmentioning
confidence: 99%